STY, a tyrosine-phosphorylating enzyme with sequence homology to serine/threonine kinases. - Howell, B W (1991)
We have cloned a novel kinase (STY) from an embryonal carcinoma cell line. Sequence analysis of the STY cDNA reveals that it shares sequence homology with serine/threonine-type kinases and yet the bacterial expression product of the STY cDNA appears to have serine-, threonine-, and tyrosine-phosphorylating activities. The predicted STY protein is highly basic and contains a putative nuclear localization signal. During differentiation, two new mRNAs were detected in addition to the embryonic transcript.